2011
DOI: 10.1002/cncr.25969
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities and socioeconomic status in men diagnosed with testicular germ cell tumors

Abstract: BACKGROUND: Previous reports indicated that African-American men with testicular germ cell tumors (TGCTs) have more aggressive tumor characteristics and less favorable outcomes than other men. The authors of this report evaluated the effects of race and socioeconomic status (SES) on stage distribution, overall mortality (OM), and cancerspecific mortality (CSM) in men with TGCTs. METHODS: The Surveillance, Epidemiology, and End Results (SEER) database was used to identify 22,553 men who were diagnosed with TGCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
51
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 36 publications
(56 reference statements)
8
51
0
Order By: Relevance
“…Given the younger ages of adolescents and men affected by TC, long-term physical and psychological outcomes must be addressed as well. As with other cancers, there is evidence that TC outcomes are worse in older persons [78] and minorities, especially African Americans [64]. Access to care and receipt of state of the art treatment should be given to ensure equitable outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Given the younger ages of adolescents and men affected by TC, long-term physical and psychological outcomes must be addressed as well. As with other cancers, there is evidence that TC outcomes are worse in older persons [78] and minorities, especially African Americans [64]. Access to care and receipt of state of the art treatment should be given to ensure equitable outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…"Low" and "High" SEP categories were created using median score as the cut point. In multivariate analysis, individuals living in areas with "Low" SEP scores (vs. "High" SEP) had significantly higher cancer-specific mortality and overall mortality HR = 1.41 (P = 0.002) and 1.28 (P < 0.001), respectively [64]. Davies et al also reported higher mortality for men with professional jobs [20].…”
Section: Sep and Survivalmentioning
confidence: 95%
See 3 more Smart Citations